Res divini juris as res extra commercium: a Comparative Analysis of Doctrine and Case Law - Anatoliy A. Lytvynenko (Právněhistorické studie)
The Roman law doctrine res extra commercium has excluded certain objects from civil-legal transactions, some of which were related to divine service or otherwise religious purposes. The Roman law doctrine designated them as res divini juris, which referred to all the objects dedicated to the Gods. The theory of res divini juris developed predominantly in civil law jurisdictions based upon the basis of the old Roman law doctrine, and could be found in legal literature, textbooks, legislation and, case law. Since the times of the Ancient Rome, the attitude to the legal status of res divini juris gradually alterated, as well as the scope of its encompassment. Despite being formally excluded from any civil-legal transactions, such objects ceased to be completely excluded from legal relationships and disputes, and are afforded with proper legal protection. Throughout the ages, courts in different states have applied and discussed the doctrine of res divini juris in various legal disputes. Complicated legal disputes concerning res divini juris also arise a question, of whether res divini juris are always res extra commercium, and if not, what are the exceptions from the rule, if any? Finally, could it be estimated, what chattels may belong to res divini juris? Do the valuable archeological findings belong to res divini juris? The article discusses the existing law doctrine of res divini juris and the applicable case law in a form of a comparative analysis in order to establish the legal status of res divini juris.